Broadcast Strategy of “Klinik 24” Program on Radio Geronimo 106.1 FM - Kalonica, Tara Putri; Nuryana, Arief; Febrianty, Yeni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Radio is an auditory medium (it can only be heard), but it is cheap, popular, and can be brought or listened to anywhere. Radio serves as a medium of expression, communication, information, education, and entertainment. The KLINIK 24 program was created to present information about trending beauty tips, trends and innovations in lifestyle, and health to listeners in the Geronimo FM segment. The material discussed in the program is about health in the form of physical, facial, internal medicine, psychology and much more about Health which is discussed in the KLINIK 24 program. This study uses a descriptive qualitative approach. Data collection techniques using observation, interviews, documentation, and literature review. The theory used to analyze is the theory of Susan Tyler Eastman's strategy. The results of this study indicate that the broadcasting strategy used by the KLINIK 24 program is a mass attracting strategy.